THE EFFECT OF THE ADDITION OF LIQUID SMOKE ON THE QUALITY OF SHREDDED TUNA (Euthynnusaffinis) DURING AT ROOM TEMPERATURE STORAGE - M. Zulfiqri; Suparmi '; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research aimed to determine the effect of liquid smoke to the quality of shredded tuna (Euthynnus affinis) during at room temperature storage. The method used in this study was experimental study by using Randomized Completely Block Design. The treatment was addition of liquid at variet composition, those were: no smoke liquid added as a control (A0), added with liquid smoke 4 ml (A1), 8 ml (A2), and 12 ml (A3), calculated based on gramsfish meat. The product of sheredded fish were stored at room temperature and observed on the right after processing, 2 weeks, 4 weeks, and 6 weeks. The parameters used in this study were the organoleptic evaluation, included: appearance, texture, odor, and flavor, followed by proximate analyses, included: moisture, protein, fat, and ash, content of total phenols and total acid, pH and the value of TBA. The results showed that the highest quality of shredded tuna fish was produced by the addition of 4 ml liquid smoke (A1), with such criteria 7.4, texture 6.7, smell 6.7, flavor 7.3, water content 8.15%, protein content 39.84, fat content 24.10%, ash content 6.0%, total phenolic 12.78%, total acid 3.92%, pH 5.69, TBA value 3.02mg malonaldehid/kg sample. TBA value indicates the addition of 4 ml liquid smoke could reduce the increase of TBA value in shredded tuna fish and so extend this shelf life.Keywords: Euthynnusaffinis, Liquid smoke, Shredded fish